Biomechanical factors and atherosclerosis localization: insights and clinical applications - Bacigalupi, Elena; Pizzicannella, Jacopo; Rigatelli, Gianluca; Scorpiglione, Luca; Foglietta, Melissa; Rende, Greta; Mantini, Cesare; Fiore, Franco M.; Pelliccia, Francesco; Zimarino, Marco (Frontiers in Cardiovascular Medicine, 2024)
Although the entire vascular bed is constantly exposed to the same risk factors, atherosclerosis manifests a distinct intra-individual pattern in localization and progression within the arterial vascular bed. Despite shared risk factors, the development of atherosclerotic plaques is influenced by physical principles, anatomic variations, metabolic functions, and genetic pathways. Biomechanical factors, particularly wall shear stress (WSS), play a crucial role in atherosclerosis and both low and high WSS are associated with plaque progression and heightened vulnerability. Low and oscillatory WSS contribute to plaque growth and arterial remodeling, while high WSS promotes vulnerable changes in obstructive coronary plaques. Axial plaque stress and plaque structural stress are proposed as biomechanical indicators of plaque vulnerability, representing hemodynamic stress on stenotic lesions and localized stress within growing plaques, respectively. Advancements in imaging and computational fluid dynamics techniques enable a comprehensive analysis of morphological and hemodynamic properties of atherosclerotic lesions and their role in plaque localization, evolution, and vulnerability. Understanding the impact of mechanical forces on blood vessels holds the potential for developing shear-regulated drugs, improving diagnostics, and informing clinical decision-making in coronary atherosclerosis management. Additionally, Computation Fluid Dynamic (CFD) finds clinical applications in comprehending stent-vessel dynamics, complexities of coronary bifurcations, and guiding assessments of coronary lesion severity. This review underscores the clinical significance of an integrated approach, concentrating on systemic, hemodynamic, and biomechanical factors in atherosclerosis and plaque vulnerability among patients with coronary artery disease.